Rhetorical Structure Analysis on Introduction Chapters of English Master Theses by Indonesian Postgraduate Students - Indah Pujiyanti; Safnil Arsyad; Arsyad, Arono A (IJEE (Indonesian Journal of English Education), 2018)
ABSTRACTThis study is aimed at investigating the rhetorical structure of Introduction chapters of English master theses written by Indonesian postgraduate students and identifying the frequency of communicative moves and their constituent steps as well as finding how the students justify their research projects reported in their Introduction chapters. The research design was mixed method research combining quantitative and qualitative method. Twenty Introduction chapters of English master theses were taken from two different fields; English language education and applied linguistics, and they were analyzed using checklists. The results: (1) three moves and fifteen steps are found in the introduction chapters of master theses and three newly identified steps other than those specified in Bunton’s are also found in the corpus of this study and (2) three moves are considered obligatory moves, seven steps are classified as obligatory, four Steps are conventional and seven Steps are optional. Further, the majority of Indonesian postgraduate students tend to rhetorically justify their research project based on the knowledge gap found in the literature. This study concludes that the move and step model suggested by Bunton (2002) and modified from Swales’ CARS is effective enough to capture the possible rhetorical structure of introduction chapter of master thesis written by Indonesian postgraduate students. ABSTRAKPenelitian ini bertujuan untuk menemukan pola retorika bab pendahuluan dalam thesis bahasa Inggris diantaranya mengidentifikasi bagian pendahuluan yang memiliki moves (tahapan), steps (langkah), dan menjustifikasi pentingnya penelitian dilakukan. Desain penelitian yang digunakan dalam penelitian ini adalah metode campuran (mixed method) yang menggabungkan kuantitatif dan kualitatif, dan instrumen utama yang digunakan dalam menganalisis data adalah instrumen ceklist. Data penelitian ini diambil dari dua bidang thesis yang berbeda; pengajaran bahasa Inggris dan fitur linguistik. Hasil dari penelitian ini: (1) tiga Moves (tahapan) dan limabelas Steps (langkah) ditemukan dalam bab Pendahuluan thesis pada penelitian ini. Selain itu, ditemukan juga tiga Steps (langkah) baru yang tidak ditemukan dalam pola Bunton (2002); (2) tiga Moves (tahapan) dikategorikan harus/wajib ada, tujuh Steps (langkah) diiklasifikasikan harus ada, empat Steps (langkah) boleh ada, dan tujuh Steps (langkah) boleh tidak ada. Selanjutnya, mayoritas mahasiswa pascasarjana Indonesia cenderung secara retoris menjustifikasi proyek penelitian mereka berdasarkan pada celah (gap) yang terdapat dalam penelitian-penelitian terkait terdahulu. Penelitian ini menyimpulkan bahwa pola tahapan (Move) dan langkah (Step) yang dikemukakan oleh Bunton (2002) dan dimodifikasi dari pola retorika Swales yakni Creating a Research Space (CARS) cukup efektif digunakan dalam menggambarkan struktur retorika bab pendahuluan pada thesis  yang ditulis oleh mahasiswa pascasarjana Indonesia.How to Cite: Pujiyanti, I. A., Arsyad, S., Arono. (2018). Rhetorical Structure Analysis on Introduction Chapters of English Master Theses by Indonesian Postgraduate Students. IJEE (Indonesian Journal of English Education), 5(2), 143-162. doi:10.15408/ijee.v5i2.8423